UK critical infrastructure is wide open to attack, warns parliamentary committee. Issue 1 (January 2019) - Unknown
Abstract : The UK Government is not doing enough to ensure that the country's critical national infrastructure (CNI) is safe from cyber attack, according to the findings of a parliamentary committee.